Identification and Quantitative Assessment of Different Components of Intracranial Atherosclerotic Plaque by Ex Vivo 3T High-Resolution Multicontrast MRI - Jiang, Y. (AJNR Am J Neuroradiol, 2017)
BACKGROUND AND PURPOSE: High-resolution 3T MR imaging can visualize intracranial atherosclerotic plaque. However, histologic validation is still lacking. This study aimed to evaluate the ability of 3T MR imaging to identify and quantitatively assess intracranial atherosclerotic plaque components ex vivo with histologic validation. MATERIALS AND METHODS: Fifty-three intracranial arterial specimens with atherosclerotic plaques from 20 cadavers were imaged by 3T MR imaging with T1, T2, and proton-density-weighted FSE and STIR sequences. The signal characteristics and areas of fibrous cap, lipid core, calcification, fibrous tissue, and healthy vessel wall were recorded on MR images and compared with histology. Fibrous cap thickness and maximum wall thickness were also quantified. The percentage of areas of the main plaque components, the ratio of fibrous cap thickness to maximum wall thickness, and plaque burden were calculated and compared. RESULTS: The signal intensity of the lipid core was significantly lower than that of the fibrous cap on T2-weighted, proton-density, and STIR sequences (P < .01) and was comparable on T1-weighted sequences (P = 1.00). Optimal contrast between the lipid core and fibrous cap was found on T2-weighted images. Plaque component mean percentages were comparable between MR imaging and histology: fibrous component (81.86% ± 10.59% versus 81.87% ± 11.59%, P = .999), lipid core (19.51% ± 10.76% versus 19.86% ± 11.56%, P = .863), and fibrous cap (31.10% ± 11.28% versus 30.83% ± 8.51%, P = .463). However, MR imaging overestimated mean calcification (9.68% ± 5.21% versus 8.83% ± 5.67%, P = .030) and plaque burden (65.18% ± 9.01% versus 52.71% ± 14.58%, P < .001). CONCLUSIONS: Ex vivo 3T MR imaging can accurately identify and quantitatively assess intracranial atherosclerotic plaque components, providing a direct reference for in vivo intracranial plaque imaging.